A SOCIO-LEGAL CRITIQUE OF ANTI-HUMAN TRAFFICKING LAWS PERTAINING TO WOMEN IN INDIA - Choudhary, Pragya; Chugh , Babita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Human trafficking, particularly of women, remains one of the gravest human rights violations in India despite a plethora of laws aimed at its eradication. This article critically examines the socio-legal dimensions of anti-human trafficking laws in India with a specific focus on women. It analyses the constitutional mandates, statutory frameworks, judicial interpretations, enforcement mechanisms, and rehabilitation policies. The paper delves into the practical challenges in implementation, the influence of patriarchal and socio-economic structures, and the limited success of the criminal justice system in offering holistic redressal. By juxtaposing legal provisions with societal realities, this article reveals the limitations of the current framework and provides recommendations for comprehensive reforms grounded in gender justice, victim-centric rehabilitation, and institutional accountability.